Determinants of Fractional exhaled Nitric Oxide (FeNO) levels in occupational asthma in different occupational settings - Mfune, Phinias Harris Katolora (Department of Public Health and Family Medicine, 2025)
Background: Fractional exhaled nitric oxide (FeNO) offers a potential tool for screening and surveillance of workers at risk of occupational respiratory allergy and asthma. Objective: This study evaluated determinants of FeNO in workers at risk of occupational respiratory allergy and asthma in diverse industries in southern Africa. Methodology: Data were analysed from cross-sectional epidemiological studies of bakery, fruit farming, spice milling, poultry farming, wood processing and healthcare industries. All studies used the modified ECRHS questionnaire, assessed atopy using Phadiatop, allergen specific sensitization (sIgE) and NIOX MINO.